Pengabdian Pengabdian kepada Masyarakat Diversifikasi Olahan Sukun (Artocarpus altilis) di Masa Pandemi Covid 19 - Sri Hartati; A. Intan Niken Tari; Retno Widyastuti (Universitas Pendidikan Muhammadiyah Sorong, 2023)
Breadfruit is very good as a food substitute and can be used as solar carbohydrates to support prospective food consumption. Duwet Village, Wonosari Subdistrict, Klaten Regency has the potential for breadfruit trees in residents' yards. However, the breadfruit produced has not been used optimally because there is still a lack of knowledge and understanding of the use of breadfruit. The purpose of this community service was to provide knowledge and skills to members of Family Empowerment and Welfare (in Indonesian is PKK) in the village. The method implemented was counseling and training. Counseling and training are carried out virtually because it was still in a state of the Covid-19 Pandemic and the implementation of Restrictions on the Movement of Community Activities (PPKM). Counseling and training begins with the preparation of video tutorials for Making Breadfruit Flour and Video Tutorials for Making Processed Breadfruit Flour. The video is uploaded to the participants' WhatsApp Group (WAG). Before and before uploading the video, the participants were given a pre-test and post-test. The results of community service activities showed that there was an increase in participants' understanding in making breadfruit flour (29.22%), and making processed breadfruit (25.18%). Increased understanding of participants has exceeded the target to be achieved. Even though using social media, the dedication was successful.